Analysis of Social Media-Based Digital Marketing and Brand Image on Buying Interest in ESQA Local Cosmetic Products - Septiani, Fanysa; Ramdan, Asep Muhamad; Danial, R. Deni Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The phenomenon of rapid growth of the cosmetics industry in Indonesia can be seen from the increase in the number of cosmetics companies and product exports. The purpose of this study is to analyze the effect of social media-based digital marketing and brand image on buying interest in ESQA local cosmetic products. The method used is quantitative with descriptive and associative approaches. Data were collected through observation, interviews, questionnaires, and literature studies, with a population of generation Z in Sukabumi City and a sample of 180 respondents. Data analysis used multiple correlation, coefficient of determination, F test, multiple linear regression, and T test. The results showed that digital marketing and brand image have a significant influence on purchase intention. The multiple correlation coefficient of 0.907 shows a very strong relationship between the independent and dependent variables. The coefficient of determination of 82,3% shows the significant contribution of digital marketing and brand image to purchase intention. The F test shows the significant effect of the independent variables simultaneously on purchase intention. Multiple linear regression shows that each unit increase in digital marketing and brand image increases purchase intention by 0.398 and 0.679, respectively. The T test shows that digital marketing and brand image partially have a significant effect on buying interest in ESQA products. In conclusion, effective digital marketing strategy and strong brand image are very important in increasing purchase intention of local cosmetic products, especially ESQA, among generation Z in Sukabumi City.